Praktik Utang Piutang pada Tradisi Buwuh Walimatul ‘Urs Perspektif Sosiologi Ekonomi Islam - Rukayati, Dewi; Dimyati, Ahmad (JIOSE: Journal of Indonesian Sharia Economics, 2025)
This study aims to find out the practice of debt and receivables in the tradition of buwuh walimatul 'urs carried out by the people of Perdopo Gunungwungkal Pati Village and to analyze the practice of buwuh in the perspective of Islamic economic sociology using the Theory of Reciprocity by Marcel Mauss. This research is a field research with a descriptive qualitative method. Data collection techniques use observation, documentation and interviews. The results of this study show that there is a shift in the tradition of buwuh walimatul 'urs of the people of Perdopo Gunungwungkal Pati Village from the original use of grant contracts to debt and receivables contracts. The transition is seen from three aspects, namely the recording of buwuh, the quantity of buwuhan given and the return of buwuhan. The transition is influenced by the reciprocity of the local community, so that every bowuhan received gives rise to the obligation to return it. This study also identified the existence of alternent reciprocity. This is a form of deviation from the theory of reciprocity, where the buwuh tradition can switch or alternate between voluntary giving (grant) and transactional giving (debt and receivable).